Al-Imam Al-Alusi Wa Mauqifuhu Min Al-Tafsir Al-'Ilmi - Muhammad Fadhli (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2018)
There are many scientific problems that had not been solved by scientists in such a long period of time. But after a deep study the scientists managed to find surprisingly all scientific matters are stated in the Qur'an. So this disputes the notion that Islam is against science and technology. An in-depth study of scientific verses is increasingly encouraged that emerges tafsir al-ilmiy. However, this effort did not escape the pros and cons among the Ulama for various reasons. But in essence the Qur'an is universal in which the verses never expire so Qur'an able to dialogue with every generation through out the ages.